Reaching Out to the Third World: East Germany's Anti-Apartheid and Socialist Human Rights Campaign. Issue 4 (19th July 2018) - Gehrig, Sebastian
Abstract: This article traces the East German encounter with anti-apartheid protests, the SED leadership's turn towards an international rights language of self-determination and against racial discrimination, and the eventual transformation of this state-mandated rights activism into socialist human rights language and advocacy for a human right of development. With formerly colonized countries' accession to United Nations membership, in the 1960s the tables within the United Nations seemingly began to turn in favour of the socialist bloc. GDR legal and foreign policy experts hoped to seize the moment and developed a comprehensive language of national self-determination and anti-apartheid to demonstrate the moral superiority of the East German socialist state over its West German neighbour. This new strategy sought to rally support from Asian and African states for the international recognition of GDR sovereignty. This GDR engagement with UN debates showcases how Third World revolutionary agendas in favour of national self-determination and against racial discrimination also reshaped European Cold War debates. The long-term conflicts over the drafting of a UN apartheid convention, which eventually was adopted on 23 October 1973, a month after both German states had gained full UN membership, facilitated the formation of East German ties to Africa. In the late 1960s and early 1970s, UN rights discourses therefore served the East German regime in many ways better than the Federal Republic. At least in the case of Cold War Germany, international rights language centred on self-determination, anti-apartheid and countering racial discrimination, and human rights had their public breakthrough largely due to socialist initiatives.